Agricultural extension among the farming community in Sri Langka - Herath, Muthubandage Mahinda; Ahmad, Nobaya; Hassan, Mohammad Mujaheed; Wan Jaafar, Wan Munira (Human Resource Management Academic Research Society, 2021)
Conventional agricultural extension approaches are insufficient to assist farmers in dealing with increasingly complex challenges in the agriculture sector. As part of the process of community development, this study aims to identify challenges among farmers and provide support for developing high-quality technologies adoption mechanisms through the community development process. This paper presents the help of conceptual applications for developing an innovative agricultural extension mechanism in Sri Lanka. It is mainly based on the following objectives; (1) to identify the structural performance of agricultural extension systems, (2) to identify achievements and constraints to improve the innovation-friendly extension process, and (3) to provide suggestions on the extension process. Preliminary results from previous studies show that the novel process influences adaptive group thinking rapidly. The integrated approach provides lessons for development and food security, and sustainability improvement. The lessons learned from this initiative can be applied to efficient participatory extension and training models. Long-term sustainable development of agricultural communities necessitates the establishment of new innovative development strategies based on a comprehensive analysis and evaluation of development resources while considering the characteristics of socio-demographic territories and strong policy development to fill gaps and expose critical information to policymakers.